The “Post-Pandemic Era” World Order and Russia’s Strategic Choice - Yujun Feng (Сравнительная политика, 2021)
The spread of COVID-19 has intensiﬁed existing global conﬂicts and profoundly changed the global political, economic, and security landscape since the end of the Cold War. Recently, Russian leaders and think tank experts have given indepth consideration to the international landscape, world order, globalization process, and major-country relations in the “post-pandemic era”. They believe that as the international pattern and world order are being reshaped at an accelerating pace, Russia is facing the greatest strategic opportunity since the Crimean crisis and even the end of the Cold War. In Russia's strategic point of view, under the new circumstances, Russia needs to reshape its foreign policy thinking, consolidate its special responsibility of the permanent members of the Security Council with the unique privileges since the founding of the United Nations, deepen Eurasian integration cooperation, skillfully manage the triangular relationship between Russia, China, and the United States, balanced relations with China by multiple forces, and strive to improve Russian-American relations.